2019
DOI: 10.1128/msystems.00124-19
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Insights in Microbial Ecological Networks from Theory to Applications

Abstract: Networks encode the interactions between the components in complex systems and play an essential role in understanding complex systems. Microbial ecological networks provide a system-level insight for comprehensively understanding complex microbial interactions, which play important roles in microbial community assembly. However, microbial ecological networks are in their infancy of both network inference and biological interpretation. In this perspective, we articulate the theory gaps and limitations in build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…To address and overcome this challenge, we developed a combined bioinformatics pipeline and network theory approach that was applied to a large, geographically diverse 16S rRNA dataset of four extreme aquatic environments to determine the ecological relevance of the unknown organisms in these communities. Although correlation-based microbial networks cannot infer the nature of ecological relationships, such as syntrophy or competition, they are indicative of social interactions within the community and can serve as important focal points for downstream analyses [54]. Our analysis clearly showed that the unclassified and uncultured taxa were prevalent and represented a significant proportion of the microbial diversity in all ecosystems examined, and therefore, should not be overlooked when examining community dynamics.…”
Section: Discussionmentioning
confidence: 78%
“…To address and overcome this challenge, we developed a combined bioinformatics pipeline and network theory approach that was applied to a large, geographically diverse 16S rRNA dataset of four extreme aquatic environments to determine the ecological relevance of the unknown organisms in these communities. Although correlation-based microbial networks cannot infer the nature of ecological relationships, such as syntrophy or competition, they are indicative of social interactions within the community and can serve as important focal points for downstream analyses [54]. Our analysis clearly showed that the unclassified and uncultured taxa were prevalent and represented a significant proportion of the microbial diversity in all ecosystems examined, and therefore, should not be overlooked when examining community dynamics.…”
Section: Discussionmentioning
confidence: 78%
“…The field of microbial networks is relatively new and should be developed based on the years of experience in studying plant and animal communities (52, . However, we still lack strong evidence of the ecological interpretation that exists in network inference, which needs more experimental verification in the future (54).…”
mentioning
confidence: 92%
“…These networks could be used to identify alternative community regimes, species interactions, and keystone species. However, their interpretation is not straightforward; while they represent an adequate tool to explore ecological associations, the implications of such associations are uncertain, and it is disputed to which degree biotic interactions can be recapitulated using available methods [70] , [71] , [72] .…”
Section: Methodsmentioning
confidence: 99%